2014
DOI: 10.1097/mnh.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

New insights regarding chronic antibody-mediated rejection and its progression to transplant glomerulopathy

Abstract: Transplant glomerulopathy is often the result of CAMR and leads to allograft loss. It is characterized by distinctive histologic changes, and its pathophysiology is a multifaceted process involving both innate and adaptive immunity. Despite advances in the understanding of this condition, no effective therapy exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…27 The TLR4 senses stimuli which contribute differently to acute kidney injury (AKI) or to CAI, and also to the development of tolerance in either NIC or bone marrowderived cells (BMDC). 23,28…”
Section: General Consequences Of Tlr4 Stimulationmentioning
confidence: 99%
“…27 The TLR4 senses stimuli which contribute differently to acute kidney injury (AKI) or to CAI, and also to the development of tolerance in either NIC or bone marrowderived cells (BMDC). 23,28…”
Section: General Consequences Of Tlr4 Stimulationmentioning
confidence: 99%
“…Studies have revealed that CAN is a leading factor, causing 50-80% of allograft loss in renal function in the late period following kidney transplantation (3,35). As CAN is caused by various immune and non-immune factors, and is easily affected by a series of donor-related factors including donor age, brain death and consequences of ischemia-reperfusion injury, the pathogenesis and mechanisms remain unclear (36)(37)(38)(39)(40). Previous studies suggested that HMGB1, which is a pro-inflammatory cytokine released from dying cells, would accumulate as renal function deteriorates and have an important role in CKD (17).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the effect of tofacitinib on NK, T, and B cells may reduce the incidence of chronic antibody mediated rejection. 37 Also, 1 experimental study in mice demonstrated that JAK3/Stat6 stimulates bone marrow-derived fibroblast activation in renal fibrosis. Treatment with tofacitinib significantly reduced myofibroblast transformation, matrix protein expression, interstitial fibrosis development, and apoptosis.…”
Section: Future Investigation In Kidney Transplantationmentioning
confidence: 99%